Designing A New Miruki Way Business Branch by Carrying Out A Feasibility Analysis - Kayla Fadiana Sofie; Endang Chumaidiyah; Nanang Suryana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Miruki Way is a culinary business located at Jl. Sukapura No. 14, Dayeuhkolot District, Bandung Regency. It offers various sweet drinks and side dishes accessible to a broad audience. The business owner was planning to open a new branch and is considering various aspects such as market analysis, technical feasibility, and financial viability. Based on the design results, the NPV value obtained using the MARR value of 10.7% is 1,151,288, the IRR value is 44.09%, and the payback period is 4.02 years. Sensitivity testing shows that the new branch is sensitive to decreasing product demand, decreasing selling prices, increasing raw materials, and increasing labor costs. Considering the risk factor of 18.37%, the NPV value is 1,496,970, the IRR value is 44.09%, and the payback period is 4.30 years. In conclusion, the branch opening is deemed feasible based on the positive NPV, IRR exceeding MARR, and the payback period falling within the expected range. Keywords: Feasibility Analysis, Market Aspect, Technical Aspect, Financial Aspect, Sensitivity and Risk Analysis